Commensal Streptococcus agalactiae isolated from patients seen at University Hospital of Londrina, Paraná, Brazil: capsular types, genotyping, antimicrobial susceptibility and virulence determinants - Otaguiri, Eliane Saori (BioMed Central, 2013)
BACKGROUND: Streptococcus agalactiae or Group B Streptococci (GBS) have the ability to access various host sites, which reflects its adaptability to different environments during the course of infection. This adaptation is due to the expression of virulence factors that are involved with survival, invasion and bacterial persistence in the host. This study aimed to characterize GBS isolates from women of reproductive age seen at University Hospital of Londrina, according to capsular typing, genetic relatedness, antimicrobial susceptibility profile and occurrence of virulence determinants. RESULTS: A total of 83 GBS isolates were enrolled in this study. Capsular types Ia (42.2%), II (10.8%), III (14.5%) and V (30.1%) were identified in most GBS. One isolate each was classified as type IX and non-typeable. A total of 15 multiple locus variable number of tandem repeat analysis (MLVA) types were identified among the isolates, seven were singletons and eight were represented by more than four isolates. All isolates were susceptible to penicillin, ampicillin, cefepime, cefotaxime, chloramphenicol, levofloxacin and vancomycin. Resistance to erythromycin and clindamycin was observed in 19.3 and 13.3% of isolates, respectively. All isolates resistant to clindamycin were simultaneously resistant to erythromycin and were distributed in the capsular types III and V. One isolate showed the constitutive macrolide-lincosamide-streptogramin B (cMLS(B)) phenotype and ten showed the inducible MLS(B) (iMLS(B)) phenotype. The mechanism of resistance to erythromycin and clindamycin more prevalent among these isolates was mediated by the gene ermA, alone or in combination with the gene ermB. The isolates displaying resistance only to erythromycin belonged to capsular type Ia, and showed the M phenotype, which was mediated by the mefA/E gene. All isolates harbored the gene hylB and at least one pilus variant, PI-1, PI-2a or PI-2b. Although cylE was observed in all GBS, four isolates were classified as gamma-hemolytic and carotenoid pigment non-producers. CONCLUSIONS: Our results indicate the potential virulence of commensal GBS isolates, reinforcing the need for continued screening for this bacterium to prevent infections. The distribution of capsular and pili antigens, and MLVA profiles was also identified, which may contribute to the development of new strategies for the prevention and treatment of GBS infection.